Leisure activities and social factors influence the generation of cultural ecosystem service benefits - McGinlay, James; Parsons, David J.; Morris, Joe; Graves, Anil; Hubatova, Marie; Bradbury, Richard B.; Bullock, James M. (Elsevier, 2018)
The relationship between cultural ecosystem services (CES) and the many diverse aspects of biodiversity is complex and multi-faceted. A large public survey in Wiltshire, UK, was used to assess associations between public benefits from certain species groups in the local countryside, and (i) social antecedents, (ii) engagement in different outdoor leisure activities (iii) indirect nature experience via media-related activities and (iv) species group charisma and abundance. Practitioners of leisure activities with a nature-related theme, whether outdoor activities or indoor media-related activities, reported significantly higher levels of benefit from named species groups, as did respondents whose personal background demonstrated an elevated degree of nature-relatedness. Benefits were also related to the charisma of the species group: enhanced benefit through nature-related activities and social factors was significant for less charismatic species, but inconclusive for more charismatic species. Respondents who participated in outdoor leisure activities without a nature focus were unlikely to report enhanced benefits from species groups in the local landscape. To maximise people’s CES benefits from broader aspects of biodiversity it may be necessary to encourage an active interest in biodiversity, leading people to participate or seek knowledge and understanding, and in turn develop a stronger sense of connectedness to nature.
Keywords: Benefits from nature; Biodiversity; Recreation; Countryside; Social antecedents; Nature connection